Human Dignity as High Moral Status - Toscano, Manuel (Les ateliers de l'éthique / The Ethics Forum, 2011)
In this paper I argue that the idea of human dignity has a precise and philosophically relevant sense. Following recent works, we can find some important clues in the long history of the term. Traditionally, dignity conveys the idea of a high and honourable position in a hierarchical order, either in society or in nature. At first glance, nothing may seem more contrary to the contemporary conception of human dignity, especially in regard to human rights. However, an account of dignity as high rank provides an illuminating perspective on the role it plays in the egalitarian discourse of human rights. In order to preserve that relational sense regarding human dignity, we can use the notion of moral status, to which some moral philosophers have paid attention in recent years. I explore the possibilities of the idea of moral status to better understand the idea of human dignity and its close relationship with human rights.